Teaching grammar to ESL adult learners / Syakirah Mohammed...[et al.] - Mohammed, Syakirah; Harun, Zetty Harisha; Harun, Robekhah (Universiti Teknologi MARA, Kedah, 2013)
Teaching adult learners in ESL classes can pose a challenge as they are very diverse in age, educational background, and employment history. They may also vary in term of interest and background knowledge. Some may have limited proficiency in English and be unable to read or write in the language; others may have college degrees and speak fluently in the language. They have very diverse experiences, especially related to the learning of English grammar. As such language instructors may face challenge in determining the grammar our adult learners need and the characteristics of language that affect the selection of grammar to teach. This paper explores what are the factors to be taken into consideration by instructors in designing lessons that will cater to the needs of adult learners.